2013
DOI: 10.5688/ajpe77353
|View full text |Cite
|
Sign up to set email alerts
|

Use of Simulation-based Teaching Methodologies in US Colleges and Schools of Pharmacy

Abstract: Objectives. To characterize the use of high-fidelity mannequins and standardized patients in US pharmacy colleges and schools. Methods. A survey instrument was sent to 105 doctor of pharmacy (PharmD) programs to collect data on the use of simulation and to identify barriers to using simulation-based teaching methods. Results. Eighty-eight colleges and schools completed the survey instrument (response rate 84%). Of these, 14 did not use high-fidelity mannequins or standardized patients within the curriculum. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
73
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 34 publications
1
73
0
1
Order By: Relevance
“…For example, Vyas and colleagues reported that 84% of US pharmacy schools use a high fidelity simulation in their curriculum. 12 However, other studies have reported conflicting results about simulation's effectiveness on student learning as compared to other teaching methodologies, so it is important to evaluate the effect of a new simulation on student learning before it is fully adopted. [13][14][15][16] In our study, MyDispense exercise-based discussion in class for a short term did not improve test scores and confidence levels compared with paper case-based discussion.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Vyas and colleagues reported that 84% of US pharmacy schools use a high fidelity simulation in their curriculum. 12 However, other studies have reported conflicting results about simulation's effectiveness on student learning as compared to other teaching methodologies, so it is important to evaluate the effect of a new simulation on student learning before it is fully adopted. [13][14][15][16] In our study, MyDispense exercise-based discussion in class for a short term did not improve test scores and confidence levels compared with paper case-based discussion.…”
Section: Discussionmentioning
confidence: 99%
“…Smaller groups also would enable faculty members to assess individual student performance. Large groups (12)(13)(14)(15)(16) were used because of the high number of IPPE students assigned to Emory Healthcare, the small number of faculty facilitators onsite, and the limited accessibility to the training domain. Another limitation was the use of a single training patient.…”
Section: Discussionmentioning
confidence: 99%
“…1 Several reports on the use of simulation have been published in the pharmacy literature, [2][3][4][5][6][7][8][9] and many colleges and schools of pharmacy use simulation to supplement IPPEs. [10][11][12][13][14] Vyas and colleagues reported 29.7% of responding schools used simulation during IPPEs. 12 Standardized patients and high-fidelity manikins are also used to supplement IPPE and demonstrate improving students' knowledge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 29.7% of the schools participating in the survey reported using simulation for IPPEs. 6 Two schools of pharmacy looked at the effects of participation in simulation activities on knowledge and skills. In 2010, University of Missouri-Kansas City School of Pharmacy described incorporating 9 hours of high-fidelity simulation involving 3 acute care cases into a longitudinal clinical IPPE that students on a satellite campus were completing in the fourth year of a 5-year professional program.…”
Section: Introductionmentioning
confidence: 99%